Applying the HIV-associated neurocognitive disorder diagnostic criteria to HIV-infected youth. (5th July 2016) - Hoare, Jacqueline; Phillips, Nicole; Joska, John A.; Paul, Robert; Donald, Kirsten A.; Stein, Dan J.; Thomas, Kevin G.F.
Abstract : Objective: The aim of this study was to apply the HIV-associated neurocognitive disorders (HAND) criteria for diagnosing HAND in HIV-infected adults, in a cohort of HIV-infected youth to thus establish whether this system is able to detect a spectrum of neurocognitive disorders (ND) in HIV-infected youth. Methods: We used a comprehensive pediatric neurocognitive battery, an assessment of functional competence, and the American Academy of Neurology system for diagnosing ND in a cross-sectional study of HIV-infected youth (n = 86) and HIV-negative controls (n = 34) to establish whether this system could detect a spectrum of ND in HIV-infected youth (6–16 years). Results: Compared to a well-matched control group of HIV-negative youth, HIV-infected youth performed significantly more poorly on tests of Verbal IQ, Full Scale IQ, processing speed, finger tapping, verbal memory, expressive language, cognitive flexibility, and inhibition. HIV-infected youth were also more likely to have impaired total competence on the Child Behavior Checklist. Using the criteria for HAND, we found that 45.35% of the 86 HIV-infected youth could be diagnosed with an ND. Furthermore, youth with HIV encephalopathy (HIVE) were 9.4 times more likely to have a diagnosis of a major ND compared to HIV-infected youth without HIVE. Conclusions: The HAND criterion designed for adults was able to identify youth with important functional cognitive impairments who do not fit criteria for HIVE and would therefore not have been identified otherwise. This has major clinical implications regarding the importance of managing HIV-infected youth.